Viral metagenomic analysis of bushpigs (Potamochoerus larvatus) in Uganda identifies novel variants of Porcine parvovirus 4 and Torque teno sus virus 1 and 2 - Blomstrom, A.L.; Stahl, K.; Masembe, C.; Okoth, Edward A.; Okurut, A.R.; Atmnedi, P.; Kemp, Stephen J.; Bishop, Richard P.; Belak, S.; Berg, M. (Springer, 2012)
Background As a result of rapidly growing human populations, intensification of livestock production and increasing exploitation of wildlife habitats for animal agriculture, the interface between wildlife, livestock and humans is expanding, with potential impacts on both domestic animal and human health. Wild animals serve as reservoirs for many viruses, which may occasionally result in novel infections of domestic animals and/or the human population. Given this background, we used metagenomics to investigate the presence of viral pathogens in sera collected from bushpigs (Potamochoerus larvatus), a nocturnal species of wild Suid known to move between national parks and farmland, in Uganda. Results Application of 454 pyrosequencing demonstrated the presence of Torque teno sus virus (TTSuV), porcine parvovirus 4 (PPV4), porcine endogenous retrovirus (PERV), a GB Hepatitis C–like virus, and a Sclerotinia hypovirulence-associated-like virus in sera from the bushpigs. PCR assays for each specific virus combined with Sanger sequencing revealed two TTSuV-1 variants, one TTSuV-2 variant as well as PPV4 in the serum samples and thereby confirming the findings from the 454 sequencing. Conclusions Using a viral metagenomic approach we have made an initial analysis of viruses present in bushpig sera and demonstrated for the first time the presence of PPV4 in a wild African Suid. In addition we identified novel variants of TTSuV-1 and 2 in bushpigs.